Correlation between solvation of peptide-resins and solvent properties - Cilli, Eduardo Maffud [UNESP]; Oliveira, E.; Marchetto, Reinaldo [UNESP]; Nakaie, C. R. (Amer Chemical Soc, 1996)
The solvation properties of model resin and peptide-resins measured in ca. 30 solvent systems correlated better with the sum of solvent electron acceptor (AN) and electron donor (DN) numbers, in 1:1 proportion, than with other solvent polarity parameters. The high sensitivity of the (AN+DN) term to detect differentiated solvation behaviors of peptide-resins, taken as model of heterogeneous and complex solutes, seems to be in agreement with the previously proposed two-parameter model, where the sum of the Lewis acidity and Lewis basicity characters of solvent are proposed for scaling solvent effect. Besides these physicochemical aspects regarding solute-solvent interactions, important implications of this study for the solid phase peptide synthesis were also observed. Each class of peptide-resin displayed a specific salvation profile that was dependent on the amount and the nature of the resin-bound peptide sequence. Plots of resin swelling versus solvent (AN+DN) values allowed the visualization of a maximum salvation region characteristic for each class of resin. This strategy facilitates the selection of solvent systems for optimal solvation conditions of peptide chains in every step of the entire synthesis cycle. Moreover, only the AN and DN concepts allow the understanding of rules for solvation/shrinking of peptide-resins when in homogeneous or in heterogeneous mixed solvents.